Pathologic Features of Colorectal Inflammatory Polyps in Miniature Dachshunds. (July 2016) - Uchida, E.; Chambers, J. K.; Nakashima, K.; Saito, T.; Ohno, K.; Tsujimoto, H.; Nakayama, H.; Uchida, K.
The histopathologic characteristics of colorectal inflammatory polyps that formed in Miniature Dachshunds were compared with those of other colorectal proliferative lesions, including adenomas and adenocarcinomas. Fifty-three colorectal polypoid lesions were histopathologically classified into inflammatory polyps (26 cases), adenoma (18 cases), and adenocarcinoma (9 cases). All 26 dogs that were diagnosed with inflammatory polyps were Miniature Dachshunds, indicating that colorectal inflammatory polyps exhibit a marked predilection for this breed. The inflammatory polyps had complex histopathologic features and were classified into 3 stages based on their epithelial composition. In early stage (stage 1), the polyps tended to exhibit a thickened mucosa containing hyperplastic goblet cells, dilated crypts filled with a large amount of mucus, and mild lymphocyte and macrophage infiltration. In later stages (stages 2 and 3), more severe neutrophil infiltration, interstitial mucus accumulation, granulation tissue, and occasional osteoid tissue were seen. Also, a few small foci of dysplastic epithelial cells were detected. The hyperplastic goblet cells, which were a major component of the epithelium of the inflammatory polyps, were positive for cytokeratin 20 (CK20), while the dysplastic epithelial cells found in inflammatory polyps (stage 3) and the tumor cells of the adenomas and adenocarcinomas were negative for CK20. These CK20-negative epithelial cells exhibited cytoplasmic and nuclear immunoreactivity for beta-catenin. In addition, the epithelial cells in the inflammatory polyps demonstrated significantly higher cyclooxygenase 2 and fibroblast growth factor 2 expression than did those of the adenomas and adenocarcinomas, suggesting that the arachidonate cascade is involved in the development of colorectal inflammatory polyps in miniature dachshunds.